Utilization of Geographical Indication Protection System for Traditional Handicrafts in Indonesia - Sugiri, Ranggalawe Suryasaladin (UI Scholars Hub, 2020)
This work attempts to analyze the implementation of the GI law and regulations in the traditional handicraft industry in Indonesia. We particularly focus on the natural and human factors that are assessed when stakeholders apply for GI registration for their traditional handicraft products. This work also analyzes the books of requirements of five handicrafts with registered GIs in Indonesia. Indonesia’s GI regulations and policies, especially with regard to handicrafts, are compared with those of India and Thailand. The article comprises four chapters. Chapter 1 introduces the topic of this work. Chapter 2 explores the protection of traditional handicrafts through GI systems. Chapter 3 details the GI law and regulations in Indonesia and the traditional handicrafts protected by GI. Chapter 4 analyzes the issue of GI registration for traditional handicrafts in Indonesia, especially the issue of the assessment of natural and human factors. The chapter also covers the comparative analysis of the GI systems implemented in Indonesia, India, and Thailand to protect traditional handicrafts. Chapter 5 summarizes our conclusions and recommendations.